Flight dynamics and parametric modeling of a 2-DOF lab aircraft. (June 2019) - Khan, Yasir Mahmood; Ahmad, Sarvat M; Ali, Mohsin; Khan, Masroor
This paper presents two degrees-of-freedom (2-DOF) modeling of a lab aircraft extending corresponding author's previous work on 1-DOF. The yaw motion is an additional DOF introduced along with the earlier work on pitch plane alone. The test-rig is designed, developed, instrumented, and interfaced with PC employing data acquisition card and real-time visualization software. Detailed mathematical models from first principles are developed incorporating important stability and control derivatives. The theoretical models are iteratively improved and validated through experimentation. The comparison reveals close agreement between math models and experimental ones. The developed high-fidelity models are to be employed for closed-loop control design and evaluation of system performance.